Family planning for women with severe mental illness in rural Ethiopia: a qualitative study - Kebede, Tigist Zerihun (Department of Psychiatry and Mental Health, 2017)
Background: Family planning is a crucial issue for all women of reproductive age, but in women with severe mental illness (SMI) there may be particular challenges and concerns. As primary care-based mental health care is expanded in low- and middle-income countries (LMICs), there is an opportunity to improve family planning services for women with SMI. However, research exploring unmet family planning needs of women with SMI in such settings is scarce. Aim: To explore the family planning experiences, unmet needs and preferences of women with SMI who reside in a predominantly rural area of Ethiopia Methods: A qualitative study design was used. Women with SMI who were participating in the ongoing population-based cohort study in Butajira were selected purposively on the basis of responses to a quantitative survey of current family planning utilization. In-depth interviews were conducted with 16 women with SMI who were of reproductive age until theoretical saturation was achieved. Audio files were transcribed in Amharic, translated into English and analysed using a Framework Approach using Open Code qualitative data analysis software. Results: The findings were grouped into four main themes. The first theme focused on the broader context of intimate relationships and sexual life of women with SMI. Sexual violence, assault and exploitation were reported by several respondents, underlining the vulnerability of women with SMI. Lack of control over sexual contact was associated with unwanted pregnancies. The second theme (childbearing and SMI) was around attitudes towards childbearing in women with SMI. Respondents described negative views from community members and some health professionals about the capacity of a woman with SMI to give birth and bring up a child. In most cases, it was assumed that a woman with SMI should not have a child at all. In the third theme (family planning for women with SMI), respondents spoke of their low access to information about family planning and systematic exclusion from existing services. In the fourth theme (preferred family planning services), the respondents had concerns about the ability of primary care workers to understand their specific family planning needs, but also valued proximity of the service and privacy. The importance of addressing health worker and community attitudes was emphasized. Conclusion: This study has provided in-depth perspectives from women with SMI about the broader context of their family planning experience, needs, barriers and how integrated primary care services could better meet their needs. Empowerment of women with SMI to access information and services needs to be an important focus of future efforts to improve the reproductive experiences of this vulnerable group.